Development of forage accumulation prediction models in tropical pastures - Tonato, Felipe; Barioni, Luis Gustavo; Pedreira, Carlos Guilherme Silveira; Dantas, Ozanival Dario; Malaquias, Juaci Vitoria (Pesquisa Agropecuaria Brasileira, 2011)
The objective of this work was to identify, quantify and model conditioning attributes of forage accumulation in Central Brazil, and to develop estimating models of the forage accumulation potential, based on climatic parameters. A database structure was modeled and implemented for forage growth data insertion. Primary data experiments with Cynodon, Panicum and Urochloa cultivars were inserted. The databank allowed the generation of sorted lists of forage mean accumulation rates (TMA), average temperature, maximum and minimum (Tmin) temperatures, global incident radiation and day of the year, for each growth period. Simple and multiple linear regressions were made, with climatic variables as regressors and TMA as response variable. The model with Tmin as independent variable was adopted as standard because it stood out for the best values of determination coefficient, Akaike criterion and Bayesian criterion. The models were grouped by the coincidence test in six groups. The models have different estimating capacities for each cultivar. Model calibration using local data can accommodate effects disregarded in its formulation, and enhances potential yield estimative accuracy.